1998
DOI: 10.1093/emboj/17.12.3484
|View full text |Cite
|
Sign up to set email alerts
|

Binary specification of nonsense codons by splicing and cytoplasmic translation

Abstract: Premature translation termination codons resulting from nonsense or frameshift mutations are common causes of genetic disorders. Complications arising from the synthesis of C-terminally truncated polypeptides can be avoided by 'nonsense-mediated decay' of the mutant mRNAs. Premature termination codons in the β-globin mRNA cause the common recessive form of β-thalassemia when the affected mRNA is degraded, but the more severe dominant form when the mRNA escapes nonsense-mediated decay. We demonstrate that cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
358
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(372 citation statements)
references
References 71 publications
14
358
0
Order By: Relevance
“…Cells were transfected with β-globin gene expression vectors encoding mRNA that was either wild-type (Norm) or harbored a nonsense mutation at codon 39 (Ter) which is an NMD target. 25,26 After a 24 h exposure to 2 μM staurosporine or DMSO, the level of globin Ter mRNA in the cells was about three times higher in the presence of staurosporine than in the presence of DMSO (Figure 5a). These results indicate that NMD is inhibited during apoptosis induced by staurosporine.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were transfected with β-globin gene expression vectors encoding mRNA that was either wild-type (Norm) or harbored a nonsense mutation at codon 39 (Ter) which is an NMD target. 25,26 After a 24 h exposure to 2 μM staurosporine or DMSO, the level of globin Ter mRNA in the cells was about three times higher in the presence of staurosporine than in the presence of DMSO (Figure 5a). These results indicate that NMD is inhibited during apoptosis induced by staurosporine.…”
Section: Resultsmentioning
confidence: 99%
“…Although all sequence variants associated with Dubin-Johnson syndrome result in the absence of a functionally active ABCC2 protein from the canalicular membrane, their effects on the synthesis and function of the ABCC2 protein differ. Premature stop codons may cause rapid degradation of the mutated ABCC2 mRNA by nonsense-mediated decay, a mechanism which cotranslationally recognizes when a stop codon precedes the last splice-site [167], thus leading to the absence of the ABCC2 protein in some cases of Dubin-Johnson syndrome. In fact, a truncated ABCC2 protein has not been detected so far [134,170].…”
Section: Transcriptional and Posttranscriptional Regulation Of Abcc2mentioning
confidence: 99%
“…Recently, Abcc2-knock-out mice have been generated and characterized by several groups [18,121,177]. These Abcc2-deficient mice are apparently healthy and fertile, as are As recommended by the Human Genome Variation Society (http://www.hgvs.org/mutnomen) and by ref [26], nucleotide position +1 is the A of the ATG of the translation initiation codon in the ABCC2 cDNA sequence, "c." describes a nucleotide change in relation to the ABCC2 cDNA sequence, "p." describes a change in relation to the deduced ABCC2 protein sequence, and "X" denotes a premature stop codon b If not indicated otherwise, the diagnosis of Dubin-Johnson syndrome was based on the histopathology of the liver and on elevated serum levels of conjugated bilirubin c PolyPhen online tool for assessing potential effects of amino acid substitutions, http://genetics.bwh.harvard.edu/pph d Single nucleotide polymorphism database, http://www.ncbi.nlm.nih.gov/SNP; data based on NCBI dbSNP build 125, regular updates available e Identified in cell lines derived from Japanese individuals f Probably reduced ABCC2 mRNA levels due to nonsense-mediated mRNA decay [167] the Abcc2-deficient rats. It will be of interest to crossbreed these mutants with mice lacking other Abc transporters, such as knock-out mice lacking Abcc3, Abcc4, Abcb1a and Abcb1b (Mdr1a and Mdr1b Pglycoprotein), and Abcg2 (Bcrp1).…”
Section: Transcriptional and Posttranscriptional Regulation Of Abcc2mentioning
confidence: 99%
“…At splicing, the exon junction complex (EJC) is deposited at the exon-exon junction, and the EJC interacts with many NMD regulation factors. If a premature termination codon is located in the 50-55 or more nucleotides upstream of the final exon-exon junction site of the gene, mRNA will be selectively degraded by the mechanisms of NMD [4][5][6]. Recent research suggested that NMD has a more important role to abolish deleterious mRNAs arising from mutations and processing errors, and regulates the overall gene expression [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was supposed that truncated mutations of γ23X and γ376X do not assemble into an intact fibrinogen molecule and are not secreted into the bloodstream. In the last decade, the presence of an RNA surveillance system has been reported, namely nonsense codon-containing mRNAs originating from genetic mutations, abnormally spliced mRNAs or some edited mRNAs are degraded by the mechanism of so-called nonsense-mediated mRNA decay (NMD) before translation [4][5][6].…”
mentioning
confidence: 99%